The Lion encyclopedia of the Bible - Alexander, Pat, 1937- (Berkhamsted : Lion Publishing, 1978)
A handbook of informative data about the people, places, and ideas i n the Bible including pertinent illustrations, photographs, maps, chart s, and diagrams.
Col. ill. on lining papers.
Includes index.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Dictionaries